Inhibition of Listeria monocytogenes on bologna by a beta acid rich hop extract. (August 2021) - Kramer, B.; Mignard, C.; Warschat, D.; Gürbüz, S.; Aiglstorfer, P.; Muranyi, P.
Abstract: Contamination of cold cuts with Listeria monocytogenes pose a risk to human health and frequently cause recalls of affected products. In order to avoid chemical additives for the preservation of ready-to-eat meat products, plant based antimicrobials are currently in demand. Beta acids from the hop plant are known for their strong antimicrobial effects especially against gram-positive bacteria like L. monocytogenes, making them a promising candidate as a functional ingredient. In this study, the antimicrobial activity of a beta acid rich hop extract in combination with sodium nitrite was characterized in vitro, at which the different hurdles of packaged cured boiled sausages were simulated. A complete growth inhibition of L. monocytogenes was found at a minimum inhibitory concentration of 0.2 μg/ml (MIC) when the hop extract was applied in combination with a reduced water activity (aw 0.970), a slightly acidic environment (pH 6) and anaerobic conditions. Under optimal growth conditions (aw 0.995, pH 7, aerobic incubation), the MIC was 16-fold higher (3.2 μg/ml). Sodium nitrite showed a comparably low antimicrobial activity against L. monocytogenes in vitro (MIC > 100 μg/ml). The presence of 1% sunflower oil negatively affected the antimicrobial activity of the hop extract, leading at least to a 32-fold increase of the MIC. The hop extract was subsequently added to a standard recipe of pork bologna at two concentrations. The pork bologna was produced by use of two different cutter processes and then sliced, inoculated on the surface with a two strain mixture of L. monocytogenes and stored at 7 °C under modified gas atmosphere for 28 days. At 0.4 g/kg of hop extract, L. monocytogenes populations were reduced up to 3 orders of magnitude in relation to bologna without hop extract while 0.8 g/kg of hop extract either prevented the growth of L. monocytogenes or resulted in at least 4 orders of magnitude lower final populations. There was no significant sensory deviation of hop bologna according to performed triangle tests (α = 0.05) and the product color remained unaffected. Based on the presented results, the use of beta acid rich hop extracts can be proposed as an additional hurdle to inhibit the propagation of L. monocytogenes on packaged ready-to-eat cold cuts like bologna. Highlights: Hurdle concept increases antimicrobial effect of hop extract. Hop extract in bologna prevents growth of Listeria monocytogenes . Hop extract could be used as functional ingredient in bologna.